The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1007/bf03007531
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative sore throat related to tracheal tube cuff design

Abstract: Recent reports of the incidence of postoperative sore throat following anaesthesia with tracheal intubation have claimed that low volume high pressure cuffs are preferable to those with high volume and low pressure. In this study similar methods were used for evaluating postoperative sore throat. Randomly selected tracheal tubes were used in 56 patients undergoing elective abdominal surgery, followed by direct questioning about sore throat on the first postoperative day. The incidence of postoperative sore thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
(3 reference statements)
1
14
0
1
Order By: Relevance
“…Among the various reasons of POST airway inflammation following airway mucosal injury, airway smooth muscle contraction contributed to the problem significantly. 4,6,8 The analgesia due to ketamine was achieved through topical action of ketamine via NMDA antagonistic action and antiinflammatory action. 14,[23][24][25][26] Experimental animal studies have shown that ketamine has protective effect on airway inflammatory injury and also relaxes airway smooth muscles probably via interference with Ca+.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the various reasons of POST airway inflammation following airway mucosal injury, airway smooth muscle contraction contributed to the problem significantly. 4,6,8 The analgesia due to ketamine was achieved through topical action of ketamine via NMDA antagonistic action and antiinflammatory action. 14,[23][24][25][26] Experimental animal studies have shown that ketamine has protective effect on airway inflammatory injury and also relaxes airway smooth muscles probably via interference with Ca+.…”
Section: Discussionmentioning
confidence: 99%
“…with a low intracuff pressure. 8 Use of topical lidocaine, 9 steroid coated tubes, 10 gargling with azulene sulphonate ketamine and licorice. [8][9][10][11][12][13] Ketamine is N-methyl daspartate (NMDA) receptor antagonist and has been used as gargle or nebulization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors contributing to the development of sore throat include trauma to pharyngolaryngeal mucosa from laryngoscopy, placement of a nasogastric tube, or oral suctioning, 2 cuff design, pressure affecting tracheal mucosal capillary perfusion 3,4 and contact of the tracheal tube with the vocal cords and posterior pharyngeal wall resulting in edema or mucosal lesions. 5 The common measures for the prevention of postoperative sore throat include the use of endotracheal tubes with a low intracuff pressure, 4,6 smaller-sized endotracheal tubes, 5 topical lidocaine, 7 steroid coated endotracheal tubes, 8 and inhalation of steroids. 9 Dexamethasone is a potent corticosteroid with analgesic, anti-inflammatory and antiemetic action.…”
mentioning
confidence: 99%
“…12 Although usually not crucial, the pain from sore throat can be the main complaint when incisional pain is well controlled, particularly by epidural analgesia. To prevent trauma to the pharynx, larynx, and trachea, various measures have been recommended, such as the use of endotracheal tubes with a low intracuff pressure, 11,13 smaller endotracheal tubes, 1 2 steroid coated endotracheal tubes, 14 inhalation of steroids, 1 5 or topical use of lidocaine. 1 6 Ketoprofen {2-(3-benzoylphenyl) propionic acid} belongs to the propionic acid derivatives, which represent a group of analgesic, anti-inflammatory, and antipyretic nonsteroidal anti-inflammatory drugs (NSAIDs).…”
mentioning
confidence: 99%